KENDALA GURU SD DALAM MENERAPKAN PENILAIAN AUTENTIK PADA IMPLEMENTASI KURIKULUM 2013 - Susilo, Susilo (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to describe the teacher's understanding of application 2013 curriculum assessment, describes the teacher's problems in implementation2013 curriculum assessment, teacher constraints and the efforts made by the teacher in overcoming the problem of the implementation of the 2013 curriculum assessment. This study used a qualitative descriptive method. The subjects of this study were 7 teachers and 1 head of Rimau Island SDN 8 in Rimau Island District. Data analysis is carried out through the steps of data reduction, data presentation, and conclusion drawing. The results of the study show that; (1) The teacher has understood the assessment and has implemented the 2013 curriculum curriculum 2013 evaluation quite well; (2) Problems faced by teachers in the application of the 2013 curriculum assessment are on the assessment of attitude competencies, knowledge competencies, and skills competencies; (3) The efforts made by the teacher to overcome the problems in the implementation of the 2013 curriculum assessment are teachers learning together and utilizing internet media, giving assignments to students to take notes of activities every day outside the classroom, the teacher asks participants to watch other friends while outside class, the teacher makes an effort toguide students who are less than the achievement, the teacher conducts a re-examination to match the students' answers.